MMP26：A Potential Biomarker for Prostate Cancer - 程腾;李飞;魏睿;吕梦琴;周颖;代芸;袁圆;蒋桂英;马丁;高庆蕾 (Current medical science, 2017)
The application of prostate-specific antigen（PSA） in the screening and diagnosis of prostate cancer（PCa） has improved the clinical management of PCa patients. However, the PSA assay has been faced with criticism due to its potential association with over-diagnosis and subsequent overtreatment of indolent patients. Matrix metalloproteinase-26（MMP26） is a member of matrix metalloproteinases（MMPs） and has been reported to be highly expressed in many cancers. This investigation evaluated the potential of serum MMP26 as a biomarker for PCa. The level of serum MMP26 was measured by enzyme-linked immunosorbent assay（ELISA） in 160 subjects including PCa group（n=80）, benign prostatic hyperplasia（BPH） group（n=40） and control group（n=40）. Furthermore, we evaluated the expression of MMP26 in tissues by immunohistochemistry. The results showed the serum MMP26 levels were significantly higher in PCa group than in BPH group and control group. Similarly, the MMP26 protein was positive in PCa tissues and negative in BPH tissues and control tissues. In conclusion, these results suggested MMP26 could be used as a potential serum biomarker in the diagnosis of PCa.